(untitled) (Bangladesh Medical Journal, 2025)
Households in rural Bangladesh face severe financial hardship due to rising healthcare costs, particularly for chronic and non-communicable diseases. This study examined the patterns of illness, treatment practices, and catastrophic health expenditure among residents of Masjidia village, Mirsharai, Chittagong. A community-based cross-sectional survey was conducted in 2016 among 152 households to retrospectively assess healthcare utilization and expenditure patterns for 2015-2016. Convenience sampling was used due to geographical constraints. Catastrophic health expenditure was defined as spending exceeding 10% of total household income. Data were collected using structured questionnaires and analyzed descriptively. Illness prevalence was 84.2% among respondents. The average annual household income was BDT 35,352, while total healthcare expenditure accounted for 52.5% of this income, exceeding the catastrophic threshold by fivefold. Medication costs were the major expense, comprising 49–82% of total healthcare spending, followed by consultation, investigation, and transport costs. Most treatments were sought from private clinics and specialists, indicating high out-of-pocket dependency. The reliance on allopathic medicine remained dominant (above 94%), reflecting both accessibility and perceived efficacy. Health spending in rural Bangladesh imposes a catastrophic financial burden on households, driven primarily by medication costs and private-sector dependence. Targeted interventions—including subsidized essential medicines, expansion of community-based insurance, and improved public primary healthcare—are essential to reduce financial vulnerability and promote equitable access. Bangladesh Med J. 2024 Sept; 53(3): 7-15